Developing Student Intelligence Based on Educational Psychology through Multiple Intelligences in the Learning Process - Husnita, Liza; Neviyarni, Neviyarni (Civiliza Publishing, Indonesia., 2025)
The problem in this research is related to the low interest in becoming a teacher among FKIP students class of 2019 at Siliwangi University. This purpose of this study was to determine the effect of personality and self-efficacy on the intention to become a teacher. The method used is a quantitative survey with an explanatory research design. The research population is the 2019 FKIP class of 1240 students. The sampling technique used was proportionate random sampling with a total of 302 respondents. The data analysis technique used is multiple regression analysis. The results of the multiple linear regression test showed Y=2.881+0.264X1+0.243X2. The results of the partial test stated that the personality variable tcount>ttable or 5.800>1.967 and a significance of 0.000<0.05, which means there is an influence on interest in becoming a teacher and self-efficacy tcount>ttable or 4.089> 1.967 and a significance of 0.000<0.05 which means there is influence on interest in becoming a teacher. Simultaneously the value of fcount>ftable or 155.535>3.025 with a significance of 0.000<0.05 means that there is a positive and significant influence between personality and Self Efficacy on the interest in becoming a teacher.